Role of ocular blood flow in normal tension glaucoma - Xingdi Wu; Katarzyna Konieczka; Xin Liu; Min Chen; Ke Yao; Kaijun Wang; Josef Flammer (Advances in Ophthalmology Practice and Research, 2022)
Background: Normal tension glaucoma (NTG) is a multifactorial disease in the pathogenesis of which intraocular pressure (IOP)-independent factors play a key role. Main text: There is considerable evidence that impairment of the ocular blood flow (OBF) is involved both in the onset and progression of this disease. With the development of the hypothesis of OBF in NTG, various imaging techniques have been developed to evaluate the OBF and blood vessels. Moreover, vascular dysregulation, which is a main factor in Flammer syndrome, was frequently observed in NTG patients. Disturbed OBF leads to increased oxidative stress, which plays an important role in the pathogenesis of glaucomatous optic neuropathy. These results suggested that IOP-independent management may provide alternative treatment options for NTG patients. Conclusions: In this review, we mainly focus on the mechanisms of the abnormal OBF in NTG.